IMPLEMENTATION OF IMMERSIVE TECHNOLOGIES IN FOREIGN LANGUAGE LEARNING: ANALYSIS OF FOREIGN AND DOMESTIC (UKRAINIAN) EXPERIENCE (Comparative Professional Pedagogy, 2022)
The use of modern immersive technologies in the educational process is due to changes in the development of information and communication technologies and the challenges of the pandemic, which forced learning and working remotely. The article summarizes the Ukrainian and foreign experience of using immersive technologies in education in general and in the process of learning foreign languages in particular. A general description of the concepts “virtual reality”, “immersion” and “immersive technologies” in the context of their use in the educational process has been presented. The advantages of using immersive technologies over traditional ones have been defined and proved. They are visibility, concentration, involvement and effectiveness It has been determined the expediency of using immersive technologies in the process of learning foreign languages as a method and technology of long-term immersion of students in a foreign language space based on a foreign language or bilingual education, which involves the use of video, audio, and text information by students to form relevant professional competencies.The research of scientists and their main results related to the selection and application of immersive technologies in teaching foreign languages have been analyzed. Virtual applications that can be used for learning a foreign language have been analyzed. The conclusion has been formulated that immersive technologies provide the formation and development of a new information method of presenting and learning educational material, which positively affects the formation of basic and professional competencies of students studying a foreign language. The opinion about the possibility of combining immersive learning methods with other interactive methods has been substantiated.
Keywords: virtual reality; immersion; immersive technologies; foreign language training; educational technology